Exploring Mycosporine-Like Amino Acids (MAAs) as Safe and Natural Protective Agents against UV-Induced Skin Damage - Anjali Singh; Mária Čížková; Kateřina Bišová; Milada Vítová (MDPI AG, 2021)
Prolonged exposure to harmful ultraviolet radiation (UVR) can induce many chronic or acute skin disorders in humans. To protect themselves, many people have started to apply cosmetic products containing UV-screening chemicals alone or together with physical sunblocks, mainly based on titanium-dioxide (TiO2) or zinc-oxide (ZnO2). However, it has now been shown that the use of chemical and physical sunblocks is not safe for long-term application, so searches for the novel, natural UV-screening compounds derived from plants or bacteria are gaining attention. Certain photosynthetic organisms such as algae and cyanobacteria have evolved to cope with exposure to UVR by producing mycosporine-like amino acids (MAAs). These are promising substitutes for chemical sunscreens containing commercially available sunblock filters. The use of biopolymers such as chitosan for joining MAAs together or with MAA-Np (nanoparticles) conjugates will provide stability to MAAs similar to the mixing of chemical and physical sunscreens. This review critically describes UV-induced skin damage, problems associated with the use of chemical and physical sunscreens, cyanobacteria as a source of MAAs, the abundance of MAAs and their biotechnological applications. We also narrate the effectiveness and application of MAAs and MAA conjugates on skin cell lines.